Pengaruh Model Problem Based Learning Berbantuan Media Chemsketch terhadap Hasil Belajar Siswa pada Materi Hidrokarbon - Maris Stella Br Purba; Ajat Sudrajat (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine whether student learning outcomes taught using the Chemsketch-assisted problem-based learning model are higher than those taught using conventional learning, and to determine student responses to the model and media applied. This study used a quasi-experimental design with a pretest-posttest control group design. Two classes were selected using purposive sampling: an experimental class using Chemsketch-assisted problem-based learning, and a control class using conventional learning. The results showed an average learning outcome of 86.80 for the experimental class and 68.05 for the control class. The analysis showed that the data were normally distributed and homogeneous. Hypothesis testing revealed a significant difference between the learning outcomes of the two classes, with the class using Chemsketch-assisted problem-based learning achieving higher learning outcomes than the conventional class. Student responses to the model and media application were in the very good category, with a percentage of 82.73%. These findings indicate that Chemsketch-assisted problem-based learning is effective in improving student learning outcomes in hydrocarbon compounds.